IMPROVING STUDENT LEARNING PROCESSES AND OUTCOMES USING THE DISCOVERY LEARNING MODEL IN SCIENCE LEARNING IN GRADE VI OF ELEMENTARY SCHOOL STATE 198/VI VILLAGE OF ULAK MAKAM: PENINGKATAN PROSES DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN IPAS DI KELAS VI SD NEGERI 198/VI DESA ULAK MAKAM - Subhanadri; Puput Wahyu Hidayat; Teha Puspita (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This classroom action research was conducted with the aim of improving the quality of the learning process and student learning outcomes in the Natural and Social Sciences (IPAS) subject through the use of the Discovery Learning model . The research was conducted at SD Negeri 198/VI Ulak Makam Village in the even semester of the 2024/2025 academic year with 20 sixth grade students as subjects, and was designed in two cycles which included the planning, action implementation, observation, and reflection stages. Data collection techniques used included learning outcome tests, teacher and student observation sheets, and documentation, where all instruments had been validated in advance by material experts and instrument experts to ensure the suitability of the material, level of difficulty, competency achievement indicators, and the accuracy of teacher performance assessments and student activities. Data analysis was carried out descriptively quantitatively and qualitatively. The results of the study showed an increase in teacher performance from 64.28% in the first meeting of cycle I to 78.57% in the second meeting, then increased further to 85.71% and 92.85% in cycle II, while student activity developed from 45% in the first meeting of cycle I to 65% in the second meeting, then increased to 80% and 90% in cycle II. The achievement of cognitive learning outcomes also experienced a significant increase, with the number of students completing from 13 people (65%) in cycle I to 17 people (85%) in cycle II, so that the research success criteria were achieved. Thus, the application of the Discovery Learning model has proven effective in creating more meaningful learning, increasing student involvement and active participation, and providing a positive impact on science learning outcomes in elementary schools, indicating that this model is worthy of being implemented sustainably in daily learning.